In the Shadow of Djoser's Pyramid : Research of Polish Archaeologists in Saqqara. - Stępień, Miłosława; Burzyński, Jan.; Myśliwiec, Karol Jan. (Frankfurt a.M. : Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2020)
Presentation of discoveries made by the Polish archaeological mission in Saqqara (Egypt) west of the Pyramid of Djoser, including cemeteries of noblemen form the Old Kingdom (the late third millennium BC) and the Ptolemaic Period (the late first millennium BC). Keywords: excavations, conservation, Old Kingdom, Ptolemaic Period, rock-hewn tombs.
Cover -- Copyright information -- Contents -- Introduction -- Bibliography -- Chronological table -- Chapter 1. History and archaeology: Saqqara in Egyptian history -- Chapter 2. From Edfu to Saqqara: Polish archaeology in the Nile Valley -- Chapter 3. First steps -- Chapter 4. The vizier's revenge -- Chapter 5. A testimony to stormy times -- Chapter 6. In the realm of Osiris -- Chapter 7. Cult of the dead -- Chapter 8. The vizier's posthumous neighbour -- Chapter 9. Behind the scenes of family bliss -- Chapter 10. Renaissance of the necropolis after two thousand years -- Chapter 11. Primum non nocere , or the medicine of artefacts -- Chapter 12. The rest is silence -- Extroduction -- Glossary of deities -- Glossary of archaeological terms -- Glossary of foreign expressions and words -- List of figures -- Figures -- Deities.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books